Feminine Spaces in Anglophone Digital Narrative - De Gregorio Robledo, Yolanda (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
Digital or electronic literature is a theoretical and creative field that, in the 1990s, began to establish itself in prominent United States universities. It developed at the start of the new millennium in the Anglo-Saxon academy and expanded to other continents, gaining ground not only in higher education institutions but also among users of new social networks. Given that this is a recently created field, we can consider that the mistakes of major literary studies, such as the neglect of female writers and the amplification of male authors over female ones, have been overcome. However, as noted by the prominent theorist N. K. Hayles, in digital literature, it remains necessary to study and bring visibility to works written by women. Therefore, the objective of this work is to shed light on the role of women in Anglophone digital narrative by presenting some of their contributions. This is intended to demonstrate the need for literary theory to continue creating study spaces in this field and to establish a canon where female writers are prominently featured. To achieve this purpose, the primary contributions made by four writers who have shaped digital narrative are presented, highlighting their significant contributions.